1996
DOI: 10.2466/pms.1996.82.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Anthropometric Characteristics of High Level Dutch Korfball Players

Abstract: In this study a morphologic and anthropometric characterisation of Dutch korfball players (N = 36) is performed. Data, compared with those of other sports populations, showed that (1) korfball athletes are smaller and lighter than basketball and volleyball players but heavier and taller than other team-sport players; (2) korfball players have less relative body fat, more lean body mass, more limb fat, and less or similar trunk fat than the other athletes. (3) Male korfball players presented a somatotype (1.9-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…According to the rules, players directly defend only players of the same sex from the opposite team to reduce the effect of height, speed, or power advantages in the game, which ensures equality. 3,4 Therefore, there may be variability in the physical structures of the athletes, especially the body composition components. Numerous studies have revealed that the physical characteristics of elite and non-elite athletes in team sports, such as body weight, lean body weight, percent fat differ significantly in body components.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the rules, players directly defend only players of the same sex from the opposite team to reduce the effect of height, speed, or power advantages in the game, which ensures equality. 3,4 Therefore, there may be variability in the physical structures of the athletes, especially the body composition components. Numerous studies have revealed that the physical characteristics of elite and non-elite athletes in team sports, such as body weight, lean body weight, percent fat differ significantly in body components.…”
mentioning
confidence: 99%
“…Numerous studies have revealed that the physical characteristics of elite and non-elite athletes in team sports, such as body weight, lean body weight, percent fat differ significantly in body components. 3,5 It has been stated that these differences may be due to firstly training and genetic equipment, nutrition, and sociocultural factors. 3 Men's and women's leagues are different in team sports other than korfball.…”
mentioning
confidence: 99%
“…The players of the korfball branch, which is one of the sports branches represented by talented athletes in international competitions in our country, has less body fat, more lean body mass, more limb fat, and less or similar body fat compared to other athletes (Godinho et al, 1996). The main catalyst in the development of Korfball sports is that boys and girls can participate in a level playing field and a cooperative and mixed sport is needed (Summerfield and White, 1989).…”
Section: Extended Abstractmentioning
confidence: 99%
“…Physical contact is not allowed in korfball sport. 7,8 In the face of intense effort, the effectiveness of athletes must be high throughout the competition. Coordinated and effective display of bio-motor properties with each other brings the condition to the fore.…”
Section: Introductionmentioning
confidence: 99%